2014 IEEE/ASME International Conference on Advanced Intelligent Mechatronics 2014
DOI: 10.1109/aim.2014.6878278
|View full text |Cite
|
Sign up to set email alerts
|

Development of delta robot driven by pneumatic artificial muscles

Abstract: Recently, research of a haptic device that renders human arbitrary-force sense has been accelerating for application in rehabilitation and virtual reality/augmented reality devices. Generally, these devices are actuated by electric motors; however, the actuators have low stiffness output and low backdrivability.In an effort to counteract these drawbacks, we developed a delta robot actuated by straight-fiber-type pneumatic artificial muscles. This robot renders human arbitrary-force sense without force sensor f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…Saikawa et al applied high-intensity longitudinal reinforced Kevlar fibers outside the silicone tube to relieve the pneumatic muscle's friction and hysteresis, but it is easy to crack [13]. Likewise, Hirano et al proposed a similar straight-fiber-type artificial muscle [14,15]. In addition, Beyl et al designed a kind of novel pleated pneumatic artificial muscle (PPM) to drive a powered knee exoskeleton (KNEXO) [16,17].…”
Section: Takedownmentioning
confidence: 99%
See 1 more Smart Citation
“…Saikawa et al applied high-intensity longitudinal reinforced Kevlar fibers outside the silicone tube to relieve the pneumatic muscle's friction and hysteresis, but it is easy to crack [13]. Likewise, Hirano et al proposed a similar straight-fiber-type artificial muscle [14,15]. In addition, Beyl et al designed a kind of novel pleated pneumatic artificial muscle (PPM) to drive a powered knee exoskeleton (KNEXO) [16,17].…”
Section: Takedownmentioning
confidence: 99%
“…A straight-fiber-type PMs-actuated 3-DOF delta mechanism was developed by Chuo University, Japan (Fig. 2 (f)) [14,15]. The arms are actuated by parallel PMs through the pulley, and the end plate always remain parallel to the base plate, to achieve three translational DOFs.…”
Section: B Parallel Rehabilitation Robotsmentioning
confidence: 99%
“…Lilly et al reported SMC maximum tracking errors of an angular antagonistic pair of PAMs to be 1.15 degrees with a 20 kg payload [19]. Hirano et al reported a maximum position tracking error of 1.17 mm for a PAM driven delta robot using a PI computed torque controller [20]. Sardellitti et al reported torque and stiffness SMC for an antagonistic pair of PAMs, which resulted in maximum errors of 0.12 N-m and 0.06 N-m/rad for torque and stiffness, respectively [21].…”
Section: Control Approaches For Pamsmentioning
confidence: 99%
“…Applications in multi-DOF systems further show the capabilities of model-based control techniques for prolate and oblate FFAs. A haptic device made using a delta robot driven by PFPAs implemented position and stiffness control with a PI computed torque and stiffness control method, resulting in an average maximum position error of 1.17 mm [21]. Sardellitti reported sliding mode torque and stiffness control for antagonistically actuated contrac-tile flexible pneumatic pairs that experimentally confirmed excellent tracking, i.e., maximum error of 0.12 N-m and 0.06 N-m/rad for torque and stiffness tracking, respectively [22].…”
Section: Introductionmentioning
confidence: 99%